2013
DOI: 10.1097/coc.0b013e3182436ea3
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy for Angiosarcoma

Abstract: For angiosarcomas treated with radiotherapy, outcome varies widely and is impacted by tumor site, size, and resectability. In amenable sites, aggressive treatment with resection and hyperfractionated radiotherapy may offer the best prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 27 publications
(95 reference statements)
0
14
0
Order By: Relevance
“…Given the poor local control with surgery alone, Scott et al reported the University of Florida experience of using hyperfractionated radiation therapy with hyperthermia for treatment of 41 angiosarcoma patients, including 16 RAA cases, and involving a variety of sites. In this series, aggressive treatment with resection and hyperfractionated radiotherapy was associated with the best prognosis [29]. Various taxane-based chemotherapeutic regimens have also shown some benefit, both in the neoadjuvant and unresectable setting.…”
Section: Discussionmentioning
confidence: 99%
“…Given the poor local control with surgery alone, Scott et al reported the University of Florida experience of using hyperfractionated radiation therapy with hyperthermia for treatment of 41 angiosarcoma patients, including 16 RAA cases, and involving a variety of sites. In this series, aggressive treatment with resection and hyperfractionated radiotherapy was associated with the best prognosis [29]. Various taxane-based chemotherapeutic regimens have also shown some benefit, both in the neoadjuvant and unresectable setting.…”
Section: Discussionmentioning
confidence: 99%
“…100 ANGIOSARCOMA MANAGEMENT By and large, angiosarcomas have a poor prognosis with reported 5-year survival rates ranging from 12% to 35%. 101 Treatment options include surgery, radiotherapy and chemotherapy, but outcomes vary widely and are impacted by site, size, resectability and tumour type (i.e. de novo vs radiation induced).…”
Section: Angiosarcoma Metastasesmentioning
confidence: 99%
“…de novo vs radiation induced). 101 Angiosarcomas of the scalp, compared with other sites, have a particularly poor prognosis with significant reduction in overall survival. Although angiosarcomas secondary to prior radiation have improved outcomes in some studies, other research contradict this finding.…”
Section: Angiosarcoma Metastasesmentioning
confidence: 99%
“…On the other hand, Ogawa et al ( 34 ) reported that in their cohort of 25 patients who received radiation monotherapy with curative intent, 11 of the 14 patients (79%) who received >70Gy achieved local control, whereas only 3 of the 11 patients (27%) who received <70 Gy did. A study by Scott et al ( 81 ) of 41 patients treated with radiation recommended at least 60–65 Gy for the postoperative tumor bed and 70–75 Gy for patients who receive radiation monotherapy. Others ( 82 ) suggested that improved delivery of radiation might achieve higher efficacy.…”
Section: Treatmentmentioning
confidence: 99%